title: Double Exponential Model author: Keith A. Lewis institute: KALX, LLC classoption: fleqn fleqn: true ...
\newcommand{\Var}{\operatorname{Var}} \newcommand{\RR}{𝑹}
The exponential random variable with parameter
Let
Exercise. Show $\int{-\infty}^\infty f(x),dx = 1$ implies $\alpha = \beta/2$_.
Hint:
This shows
The moment generating function of
Exercise. Show $E[e^{sX}] = \beta^2/(\beta + s)(\beta - s)$, $s < \beta$.
Hint: Use
Solution
$$ \begin{aligned} E[e^{sX}] &= \int_{-\infty}^\infty e^{sx} e^{-\beta |x|}\beta/2\,dx \\ E[e^{sX}] &= \int_{-\infty}^0 e^{sx} e^{\beta x}\beta/2\,dx + \int_0^\infty e^{sx} e^{-\beta x}\beta/2\,dx \\ &= \frac{\beta}{2}\bigl(\frac{1}{\beta + s} + \frac{1}{\beta - s}\bigr) \\ &= \frac{\beta}{2}\bigl(\frac{1}{\beta + s} + \frac{1}{\beta - s}\bigr) \\ &= \frac{\beta^2}{(\beta + s)(\beta - s)} \\ \end{aligned} $$The cumulant of
Note
Exercise. Show $\kappa'(s) = -1/(\beta + s) + 1/(\beta - s)$, $s < \beta$.
Solution
$$ \begin{aligned} \kappa'(s) &= -1/(\beta + s) + 1/(\beta -s) \\ &= -1/(\beta + s) + 1/(\beta - s) \\ \end{aligned} $$The mean of
The variance of
Exercise. Show $\Var(X) = 2/\beta^2$, $s < \beta$.
This shows
Solution
$$ \begin{aligned} \kappa''(s) &= 1/(\beta + s)^2 + 1/(\beta - s)^2 \\ \end{aligned} $$Valuing options and their greeks with underlying
Exercise. If $x \le 0$ then $\Phi(x, s) = (1 - s/\beta) e^{(s + \beta)x}/2$.
Hint: Use
Solution
$$ \begin{aligned} \Phi(x, s) &= E[e^{sX - \kappa(s)} 1(X \le x)] \\ &= e^{-\kappa(s)} e^{(s + \beta)x}(\beta/2)/(s + \beta) \\ &= \frac{(\beta + s)(\beta - s)}{\beta^2} e^{(s + \beta)x}(\beta/2)/(s + \beta) \\ &= \frac{(\beta - s)}{\beta} e^{(s + \beta)x}/2 \\ &= (1 - s/\beta) e^{(s + \beta)x}/2 \\ \end{aligned} $$Note
If
Exercise. If $x \ge 0$ then $\Phi(x, s) = 1 - (1 + s/\beta) e^{(s - \beta)x}/2$, $s < \beta$.
Solution
$$ \begin{aligned} \Phi(x, s) &= \Phi(0, s) + \int_0^x e^{su - \kappa(s)} e^{-\beta u}\beta/2\,du \\ &= \Phi(0, s) + e^{-\kappa(s)} \bigl(e^{(s - \beta)x}/(s - \beta) - 1/(s - \beta)\bigr)\beta/2 \\ &= \Phi(0, s) + \frac{(\beta + s)(\beta - s)}{\beta^2} \bigl(e^{(s - \beta)x}/(s - \beta) - 1/(s - \beta)\bigr)\beta/2 \\ &= \Phi(0, s) - \frac{(\beta + s)}{\beta} (e^{(s - \beta)x} - 1)/2 \\ &= \Phi(0, s) - (1 + s/\beta) e^{(s - \beta)x}/2 + (1 + s/\beta)/2 \\ &= (1 - s/\beta)/2 - (1 + s/\beta) e^{(s - \beta)x}/2 + (1 + s/\beta)/2 \\ &= 1 - (1 + s/\beta) e^{(s - \beta)x}/2 \\ \end{aligned} $$Note